Pathological internet use in adolescents - Hüseyi̇n Dağ; Murat Coşkun (Universitas Negeri Padang, 2021)
Internet addiction, which is one of the handicaps seen as a result of modern lifestyle and technological development, can be defined as the inability to prevent the desire to use the internet excessively and the need for more and more time spent on the internet. Rather than banning the internet entirely, controlling its use is a more appropriate option. As in all addictions, when the problem cannot be solved, it is important to benefit from medical and cognitive therapies and, when appropriate, child and adolescent mental health counseling.